Pembelajaran Tatap Muka di Tengah Pandemi Covid 19 (Penelitian di Madrasah Tsanawiyah Al Huda Al Musri 1 Cianjur) - Muhammad Makky; Supiana Supiana; Qiqi Yuliati Zaqiyah (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2022)
The emergence of the Covid 19 pandemic caused some educational institutions to decide to carry out online learning. However, Madrasah Tsanawiyah Al Huda Al Musri 1 Cianjur became one of the educational institutions that continued to carry out face-to-face learning during the Covid 19 pandemic. This article aims to describe the policy of implementing face-to-face learning in the midst of the Pandemic, the impact of face-to-face learning policies in the midst of the pandemic, as well as supporting factors and inhibiting the policy of face-to-face learning activities in the midst of the Covid 19 pandemic in Madrasah Tsanawiyah Al Huda Al Musri 1 Cianjur. This paper was compiled using a case study approach in qualitative research methods, primary data sources obtained from principals, teachers and students of Madrasah Tsanawiyah Al Huda Al Musri 1 and secondary data sources from madrasah documentation Tsanawiyah Al Huda Al Musri 1. Data collection techniques are used in the form of interviews, observations and documentation with three methods of data analysis, namely data reduction, data presentation and conclusion withdrawal. Face-to-Face Learning in the Midst of the Covid 19 Pandemic in Madrasah Tsanawiyah Al Huda Al Musri 1 is carried out by reducing the duration of learning so that it has an impact on the addition of activities outside the classroom, but parents benefit because their children still receive learning safely. Supporting the implementation of this learning is the existence of a 24-hour dormitory system and the inhibiting factor is the lack of facilities and infrastructure.